Prevalence of Obesity and its Relationship with Birth Weight among High School Female Students in the City of Yazd - Azadeh Nadjarzadeh; Niloofar Sadat Sadri Moghadam; Hassan Mozaffari-Khosravi; Farimah Shamsi (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: The idea that factors during early critical periods of life affect on long term health is now a major public health concern. In this study, in addition to investigating obesity prevalence among female high school students in Yazd, the relationship between obesity and birth weight was examined. Materials and Methods: This cross sectional study was conducted on 312 female high school students. Random cluster sampling method was done among 6 high schools from two education districts in Yazd. According to the birth weight recorded on their growth cards, the students were divided to 3 weight groups of low birth weight (4000 g). Anthropometric measurements including weight, height and waist circumference were alsocarried out. In terms of the percentiles proposed by NCHS, BMI was considered as light weight (5th percentile≤), normal (5-85th percentile), overweight (85-95th percentile) and obese (95th percentile≥). In addition, 95th percentile≥for waist circumference was considered abdominal obesity. Finally, the data were analyzed by SPSS 16 software. Results: The samples' mean weight and BMI were higher than 50th percentile of NCHS and their mean height was lower than 50th percentile of NCHS. Based on the results, 5.7% of the samples were underweight, 73.4% were normal, 17.1% were overweight and 3.8% were obese. Abdominal obesity rate was measured as 18.7%. There was a significantly positive correlation between birth and current weight of students (p= 0.001 and r= 0.2) and their BMI (p= 0.005 and r= 0.15). Conclusion: Relatively high prevalence of obesity and overweight in this study and its positive relationship with birth weight necessitate preventive strategies and training during and even before pregnancy by relevant authorities for women at gestational age and other related groups.